Research on Public Management Strategy of Optimizing the Service Efficiency of NHS System in Britain - Liang, Hanzhong (International Journal of Social Sciences and Public Administration, 2024)
In this paper, the optimization of the service efficiency of the National Health Service (NHS) in Britain is deeply discussed, and the corresponding public management strategies are put forward. In order to improve the service efficiency of NHS system, this paper puts forward a number of public management strategies. First of all, improve the management system, introduce performance evaluation mechanism and strengthen cross-departmental cooperation to motivate medical service providers and managers to improve their work efficiency. Secondly, optimize the allocation of resources, dynamically adjust the allocation of medical personnel and beds according to seasonal and regional needs, and improve the efficiency of human resources. Finally, strengthen information construction, promote electronic medical record system, and use big data and artificial intelligence technology to improve the accuracy and efficiency of medical services. By drawing lessons from successful public management strategy cases at home and abroad, this paper provides practical reference for optimizing the service efficiency of NHS system. The British government and relevant institutions should formulate detailed implementation plans to ensure that these strategies are effectively implemented, so as to improve the overall service level and patient satisfaction of the NHS system. The research in this paper provides valuable insights and strategic suggestions for optimizing the service efficiency of NHS system in Britain, which is of great significance for improving the quality and efficiency of medical services.